Case report: Generalized bullous fixed drug eruption mimicking epidermal necrolysis - Paulmann, Maren; Reinkemeier, Felix; Lehnhardt, Marcus; Mockenhaupt, Maja (Frontiers in Medicine, 2023)
Generalized bullous fixed drug eruption (GBFDE) is the most severe form of fixed drug eruption and can be misdiagnosed as epidermal necrolysis (EN). We report the case of a 42-year-old male patient presenting with more than 50% skin detachment without defined areas of exanthema or erythema and a history of one prior event of EN caused by acetaminophen (paracetamol), allopurinol, or amoxicillin 1.5 years ago. The initial diagnosis was GBFDE or EN. The histology of a skin biopsy was unable to distinguish between the two diseases. The course of the disease, the later clinical presentation, and the medical and medication history, however, were in favor of a diagnosis of GBFDE with two potentially culprit drugs: metamizole and ibuprofen. Moxifloxacin, enoxaparin sodium, hydromorphone, and insulin human were administered concomitantly, which makes them suspicious as well. Unfortunately, the patient received an additional dose of metamizole, one of the possible causative drugs, and he developed another bullous reaction within 1 month. This led to the diagnosis of GBFDE due to metamizole. This report highlights the challenges of distinguishing two rare diseases and elucidates the importance of distinct clinical presentation and detailed medication history.